Training and Mentoring on Clean Water Treatment System Development for Batulappa Teachers and Students. - Andi Irwandi; Fatma; Suryani Syahrir; Ahmad Swandi; Sri Rahmadhanningsih; Andio Calen Evains (Universitas AMIKOM Yogyakarta, 2026)
This Community Service Program addressed limited access to clean water at SDN 219 Kassa, which resulted in poorly functioning toilet facilities and underutilized school land for reforestation. These conditions affected hygiene, health, and ecological awareness among school residents. The program aimed to: (1) enhance teachers’ and students’ skills in clean water processing using appropriate technology; (2) install a simple water treatment system for toilets and irrigation; (3) promote productive land use through reforestation; and (4) foster ecological awareness and environmental independence. Activities included socialization, training, technology implementation, mentoring, and evaluation. A biofilter-based water treatment installation with a capacity of ±50 liters/minute was constructed, supported by a drilled well and water tank. A school gardening program was also implemented, planting kangkung, mustard greens, tomatoes, chilies, and eggplant managed by teachers and students. Results show significant skill improvement, with average scores increasing from 47.5 (low) to 79.5 (good). The water system functions effectively for sanitation and irrigation, while school land is now used as a productive garden and contextual learning resource. Initial harvests are projected to reach ±107 kg by December 2025 for school consumption or small-scale entrepreneurship.